1986
DOI: 10.1093/carcin/7.6.859
|View full text |Cite
|
Sign up to set email alerts
|

In vitro DNA-binding of microsomally-activated fluoranthene: evidence that the major product is a fluoranthene N2-deoxyguanosine adduct

Abstract: Incubation of 3-[3H]fluoranthene with a rat liver microsomal activation system in the presence of calf thymus DNA resulted in radioactivity bound to the DNA. The fluoranthene-modified DNA was enzymatically digested and a DNA adduct elution profile developed using h.p.l.c. The fraction containing the major fluoranthene--DNA adduct was further purified by h.p.l.c. and separated into two subfractions. Treatment of these with perchloric acid liberated guanine in both cases. Evidence that both were N-2 guanine deri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

1990
1990
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(15 citation statements)
references
References 0 publications
0
15
0
Order By: Relevance
“…This diol undergoes further metabolism to form syn-and anti-FLA 2,3-diol-1,10b-epoxides. Published reports have further shown that FLA 2,3-diol-1,10b-epoxide contributes to significant DNA binding [40]. Other oxidation pathways of this diol may yield FLA 2,3-dione and FLA 7,8-diol [28].…”
Section: Discussionmentioning
confidence: 97%
“…This diol undergoes further metabolism to form syn-and anti-FLA 2,3-diol-1,10b-epoxides. Published reports have further shown that FLA 2,3-diol-1,10b-epoxide contributes to significant DNA binding [40]. Other oxidation pathways of this diol may yield FLA 2,3-dione and FLA 7,8-diol [28].…”
Section: Discussionmentioning
confidence: 97%
“…While colon cells could metabolize FLA, the generation of FLA 2,3-diol in greater proportions when cells were treated with FLA together with BaP is noteworthy due to the ability of this metabolite to bind to cellular macromolecules such as DNA and proteins (Babson et al, 1986; Hutchins et al, 1988). …”
Section: Discussionmentioning
confidence: 99%
“…While colon tumor microsomes were able to produce FLA metabolites, the generation of FLA 2, 3-diol in greater proportions in microsomal incubations of FLA with BaP assumes importance given the ability of this metabolite to bind to cellular macromolecules such as DNA and proteins [41, 42]. Therefore, it is reasonable to speculate that BaP pretreatment may enhance the generation of reactive metabolites of FLA which in a dual or sequential exposure scenario may influence tumor progression.…”
Section: Discussionmentioning
confidence: 99%